Future teachers training for organization of pupils’ moral education (Pedagogy of Higher and Secondary Education, 2015)
Pidborskyi Yu. G. Future teachers training for organization of pupils’ moral education.In the paper the questions of future teachers training for organization of moral education at comprehensive school, as well as questions of training of teaching staff of new generation are examined. Activity features of subjects of a moral education; ways of the maximum activization of pupils as subjects of education process; forms and methods of education which are based on the human relations of teachers and pupils are given.
Keywords: teachers; teacher’ professional training; moral education of students; secondary school